Preparation and characterization of supported nano-zero valent iron for treatment of organic pollutants in water - Atyaf Khalid Hammed, Al-Dahan (2017)
The presence of hazardous organic pollutants in water stream creates the environmental and health problems. Thus, efficient removal approach is required. One of the relatively simple and cost effective approaches is through adsorption process in the presence of nano-adsorbent such as Nano Zero Valent Iron (NZVI). However, NZVI has several major restrictions such as agglomeration, low durability, and poor mechanical strength which would affect its adsorbent efficiency. In order to overcome these problems, supported Nano Zero Valent Iron (NZVI) has been introduced either on untreated or carbon-coated supporting materials. The preparation of carbon-coated supporting materials involved chemical functionalization via wet impregnation method by D-glucose as a carbon source followed by carbonization step at different temperature. The prepared adsorbents are characterized by XRD, FTIR, N2-Physisorption, TGA, FESEM-EDX and TEM. It was found that the carbonization temperature is crucial for obtaining good coverage of carbon coating material and in this case, 500ºC is the optimum temperature. The feasibility of employing these nano-adsorbents in the removal of the three selected adsorbates (methylene blue (MB), 2, 4, 6-Trichlorophenol (TCP) and chloroform (CHCl3) from aqueous solution is investigated in a series of batch experiments. In general, carbon-coated adsorbent produces higher adsorption capacity as compared to chemically modified adsorbents. The adsorption parameters (e.g. equilibrium time ranging between 0-180 min, the adsorbents dosage ranging between 0.05-0.1g, the initial concentration ranging between 10-40mg/L, the temperature ranging between 30-50ºC and the pH of solution ranging between 2-9) are established for all adsorbents. Then, the mechanism of the adsorption process is determined based on the Freundlich and Langmuir isotherm models and found that the Freundlich is a better fit with MB adsorption. The maximum adsorption uptakes (qmax) calculated by Langmuir isotherm model for carbon-coated adsorbent were found to be higher for all three tested adsorbates than those of uncoated supports adsorbents. For instance, in case of MB removal, 80% increment in qmax value was obtained for NZVI/SuZSM as compared to uncoated adsorbent counterpart. It is believed that the superior adsorption performance of carbon-coated adsorbent is due to the synergistic effect between the availability of functionalized active adsorption sites with porosity characteristics of supporting materials as well as the stability of NZVI nanoparticles. Besides, the kinetics of the adsorption process is well described by the pseudo-first and second order kinetics models and found the second order is the best fit for the three adsorbates on the all tested adsorbents. The thermodynamic studies for three adsorbates are performed to determine the free energy (ΔGᵒ), enthalpy (ΔHᵒ) and entropy (ΔSᵒ) and found the spontaneity of CHCl3 with negative value of (ΔGᵒ) onto all tested adsorbent, while non-spontaneity process at 30ºC with positive value of (ΔGᵒ) for adsorption of MB onto NZVI/ZSM and for TCP adsorption onto NZVI/MSN and NZVI/ZSM, respectively. In general, the current study confirms that the developed adsorbents are stable with high adsorption capacity as well as can be regenerated for subsequent adsorption process without appreciable loss of adsorption efficiency.